2021
DOI: 10.3390/jcm10163702
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Severe Hypothermia and Its Impact on Postoperative Surgical Complications and Time Delay to Adjunct Treatments in Breast Surgery Cancer Patients: A Case-Controlled Study

Abstract: Introduction: Unintended postoperative hypothermia frequently occurs upon arrival in the post anesthesia care unit (PACU). As part of our quality assurance program in anesthesia, we regularly monitor the incidence of this complication through our anesthesia information management system (AIMS). In this case-controlled retrospective study, our goal was to detect the incidence of unintended severe hypothermia in our breast surgery cancer patients, and subsequently to analyze the consequence of this complication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…In breast cancer surgery, a study conducted by Motamed et al showed no difference in complication/infection, nor did it show a delay to adjuvant radiation therapy or chemotherapy for patients who experienced hypothermia. 28 There are also studies that link the use of ADM and radiation therapy to increased likelihood of SSI in the breast cancer reconstruction patient population; however, in our study, we found no significant difference between the two cohorts with respect to the use of ADM or rates of chemotherapy/radiation therapy, making it unlikely that these variables impacted the results of our study, indicating that hypothermia increased the likelihood of SSI in this population. 9,29 Another potential, anecdotal source of SSI in this patient population is the use of forced-air warmers; however, the literature is conflicting on the use of forced-air warmers and SSI.…”
Section: Discussioncontrasting
confidence: 69%
“…In breast cancer surgery, a study conducted by Motamed et al showed no difference in complication/infection, nor did it show a delay to adjuvant radiation therapy or chemotherapy for patients who experienced hypothermia. 28 There are also studies that link the use of ADM and radiation therapy to increased likelihood of SSI in the breast cancer reconstruction patient population; however, in our study, we found no significant difference between the two cohorts with respect to the use of ADM or rates of chemotherapy/radiation therapy, making it unlikely that these variables impacted the results of our study, indicating that hypothermia increased the likelihood of SSI in this population. 9,29 Another potential, anecdotal source of SSI in this patient population is the use of forced-air warmers; however, the literature is conflicting on the use of forced-air warmers and SSI.…”
Section: Discussioncontrasting
confidence: 69%
“…26 In addition, intraoperative hypothermia has been linked to delayed hospital discharge. 27 In this study, we could not establish a statistical correlation between hypothermia and wound complications, such as wound dehiscence or wound infection. Previous experimental and clinical studies have investigated the influence of hypothermia on microvascular complications.…”
Section: Discussionmentioning
confidence: 79%
“…When examining the plastic surgery and breast cancer surgery literature, there are multiple studies looking at the effect of hypothermia. In a previous study, patients who experienced perioperative hypothermia in breast cancer surgery did not have any long-term complications with regard to SSI or delay to adjuvant radiation/chemotherapy 37 . In elective plastic surgery, there are conflicting studies with some demonstrating no differences in postoperative outcomes and others finding increased risk of seroma formation, longer recovery times, higher pain scores, and increased usage of opioids 38–41 .…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, patients who experienced perioperative hypothermia in breast cancer surgery did not have any long-term complications with regard to SSI or delay to adjuvant radiation/chemotherapy. 37 In elective plastic surgery, there are conflicting studies with some demonstrating no differences in postoperative outcomes and others finding increased risk of seroma formation, longer recovery times, higher pain scores, and increased usage of opioids. [38][39][40][41] While these studies primarily include body contouring patients, they support the findings of this study.…”
Section: Discussionmentioning
confidence: 99%